The necessity of nature : God, science and money in 17th century English law of nature - García-Salmones Rovira, Mónica (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2023)
"This is a study of the philosophy and theology of the Scientific Revolution and its impact on European natural law and political liberalism. It analyses transformations of the concept of sacred nature and the human light of reason leading to the Anthropocene, and fluctuations between human necessities and scientific money"--
A Christian science : searching for the common good and the public good -- Hobbes's doctrine of necessity -- Necessities, natural rights and sovereignty in Leviathan -- Reformers on the necessary knowledge -- Necessity, free will and conscience : Robert Sanderson -- The grand business of nature -- Robert Boyle, the empire over nature -- Locke's early writings -- Medicine, oeconomy and needs -- Money and the doctrine of necessities -- The scientification of money -- The doctrine of necessities and the (public) good -- Conclusions.
Sisältää bibliografisia viitteitä ja hakemiston.
Keywords: 1600-luku; historia; lait; luonnonoikeus; luonto; tieteellinen maailmankuva; tiede; teologia; talous; oikeusjärjestys; Natural law -- History -- 17th century; Natural law -- England -- History -- 17th century; Englanti